1905 Mo. Laws 161 - (:unkn) unknown (My University, 1905)
An Act Relating to the Preservation, Propagation and Protection of Game Animals, Birds and Fish, Creating the Office of Game and Fish Warden, Creating a Game Protection Fund, and Appropriating Money Therefrom, § 11: Any person who, in the pursuit of any wild duck, goose, brant, or other aquatic bird, upon the waters of this state, shall use any sneak boat, or any sail boat, or boat propelled by steam, naptha, electric or other engine or machinery, or any battery, swivel gun or punt gun, or who shall kill or attempt to kill or to pursue, while occupying or using any such boat, any wild geese, duck, brant, or other aquatic bird, or who shall construct or use for the purpose of hunting, upon the ice any fixed or artificial blind or ambush, shall be punished by a fine of not less than $10.00 nor more than $50.00.
Keywords: HUNTING REGULATION